The Coyote Universe. I. Precision Determination of the Nonlinear Matter Power Spectrum - Heitmann, Katrin; White, Martin; Wagner, Christian; Habib, Salman; Higdon, David (The Astrophysical journal, 2010)
Near-future cosmological observations targeted at investigations of dark energy pose stringent requirements on the accuracy of theoretical predictions for the nonlinear clustering of matter. Currently, N-body simulations comprise the only viable approach to this problem. In this paper, we study various sources of computational error and methods to control them. By applying our methodology to a large suite of cosmological simulations we show that results for the (gravity-only) nonlinear matter power spectrum can be obtained at 1% accuracy out to k {approx} 1 h Mpcsup -1. The key components of these high accuracy simulations are precise initial conditions, very large simulation volumes, sufficient mass resolution, and accurate time stepping. This paper is the first in a series of three; the final aim is a high-accuracy prediction scheme for the nonlinear matter power spectrum that improves current fitting formulae by an order of magnitude.